Counterpoint. (London : Gimpel Fils, 1990)
Hiller, Susan ; Francis, Sam ; Klein, Astrid ; Art in Ruins ; Klein, Yves ; Toren, Amikam ; Duchamp, Marcel ; Atkinson, Terry ; Warhol, Andy ; Andre, Carl ; Fisher, Andrea ; Holzer, Jenny ; Art & Language ; James, Andrew ; Wall, Jeff
Counterpoint, Gimpel Fils, London, 14 November 1990 - 12 January 1991
boek